Analysis of Financial Performance of Conventional and Islamic BUMN Banks Before and During the Covid-19 Pandemic - Hendrik Suhendri; Risna Ningsih; Irenius Iyel (MEC-J (Management and Economics Journal), 2022)
Almost all economic sectors in the world have been affected by the Covid-19 pandemic, including the national banking industry in Indonesia. This study purpose was to examine the differences in the financial performance of State-Owned Conventional Banks and State-Owned Sharia Banks before and during the Covid-19 pandemic. The assessment of financial performance uses the CAR ratio, NPL ratio (for conventional banking) and NPF ratio (for Sharia banking). The database used is the 2019 and 2020 banking financial reports in the website of Financial Services Authority and the websites of each bank. Based on purposive sampling technique, the selected banks that meet the criteria are BRI bank, Mandiri bank, BNI bank, BTN bank, BRI Syariah bank, BNI Syariah bank, and Syariah Mandiri bank. The results of paired sample t test analysis showed that Ho was accepted, meaning that there was no difference in the performance of Capital Adequacy Ratio at SOCB before and during the Covid-19 Pandemic. The analysis of paired sample t test for SOSB, which is seen from the CAR, shows that there is no difference in the performance of CAR ratio of SOSB before and during the Covid-19 pandemic. This indicates that both SOCB and SOSB can maintain their capital adequacy ratio. Conversely, the performance of SOCB credit financing (NPL), using the paired sample t test, shows that there is a difference in the NPL performance of SOCB before and during the Covid-19 pandemic. Meanwhile, contrary to the NPL results of SOCB, the NPF of SOSB shows no difference, both before the Covid-19 pandemic and during the Covid-19 pandemic. This indicates that the performance of SOSB credit financing (NPF) is relatively safe compared to the performance of  SOCB (NPL) credit financing.